2016
DOI: 10.1177/1933719116643594
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Cell-Penetrating Peptide-Conjugated Estrogen-Related Receptor β Improves the Formation of the Inner Cell Mass and the Development of Vitrified/Warmed Mouse Embryos

Abstract: Estrogen-related receptor β (ESRRB), which is a member of the nuclear orphan receptor family, regulates the messenger RNA (mRNA) expression levels of the transcription factors, Oct4 and Nanog, in early embryos and germ cells, thereby maintaining the undifferentiated state and pluripotency of the relevant cells. The present study was designed to determine whether the upregulation of pluripotency-related genes by direct delivery of ESRRB protein may affect on the commitment into inner cell mass (ICM) or the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…1C), suggesting that EpCAM is a zygotic activated gene. We noticed that the high level expression of zygotic activated pluripotent genes LIN28 30 and ESRRB 31 was also presented at the morula stage in in vivo embryos though the expression profile of pluripotent genes displayed the slightly different expression patterns in in vitro embryos. Being consistent with the transcriptomic and RT-PCR analyses, immunofluorescence staining confirmed that EpCAM protein was expressed and translocated to the cellular membrane in piPSCs, but was undetectable in non-reprogrammed PEF cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…1C), suggesting that EpCAM is a zygotic activated gene. We noticed that the high level expression of zygotic activated pluripotent genes LIN28 30 and ESRRB 31 was also presented at the morula stage in in vivo embryos though the expression profile of pluripotent genes displayed the slightly different expression patterns in in vitro embryos. Being consistent with the transcriptomic and RT-PCR analyses, immunofluorescence staining confirmed that EpCAM protein was expressed and translocated to the cellular membrane in piPSCs, but was undetectable in non-reprogrammed PEF cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, it has been generally accepted that the vitrification procedure can maintain the developmental capacity of mammalian oocytes after cryopreservation and contribute to the preservation of female fertility (Practice Committees of American Society for Reproductive Medicine and Society for Assisted Reproductive Technology, 2013). However, some effects of cryo-injury still must be overcome in conventional and cloned embryos, even if various technologies are applied (Baek et al., 2017, Yang et al., 2016). To test whether increased histone demethylation has an effect on the recovery of diminished reprogramming potential mediated by cryo-injury, we injected Kdm4a mRNAs into cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…We thus subsequently applied recombinant CPP-CARM1 protein directly to cloned mouse embryos. Support for this strategy is provided by our previous report showing that CPP-conjugated ESRRB, a member of the orphan nuclear receptor families, improved the developmental potential of cryopreserved mouse embryos and increased expression of the transcription factors Oct4 and Nanog 25 . In addition, supplementation of culture medium with CPP-ESRRB protein has been shown to enhance the function of ICM in fresh embryos increasing Oct4 gene expression 24 .…”
Section: Discussionmentioning
confidence: 98%
“…Lim and colleagues also identified a new form of CPP, obtained from human papillomavirus L1 capsid protein (LDP12), and confirmed its ability to deliver a fusion protein of enhanced green fluorescence protein and MAP1LC3 (EGFP-LC3) into mouse blastocysts 23 . In our previously reports, the cell number of inner cell mass (ICM) and expression of the Oct4 gene were positively regulated in fresh and cryopreserved embryos after treatment with CPP-conjugated estrogen-related receptor β (CPP-ESRRB) during in vitro cultivation 24 , 25 . In the present study, we provide the first demonstration that exogenous supplementation with a novel CPP-conjugated CARM1 improves the normally poor embryonic development of cloned mouse embryos through regulation of gene expression.…”
Section: Introductionmentioning
confidence: 97%